The five-factor model, stock returns and idiosyncratic volatility: evidence from Sri Lanka - Perera, H.A.P.K. (University of Jaffna, 2022)
Traditionally, the success of asset pricing models is assessed in the absence of idiosyncratic volatility, as it is believed that the role of idiosyncratic volatility is irrelevant. Nevertheless, the existing literature shows that idiosyncratic volatility matters in asset pricing decisions. Hence, this study aims to test the performance of the five-factor asset pricing model of Fama and French (2015) in the presence of idiosyncratic volatility. This study utilizes a sample of 214 companies listed on the Colombo Stock Exchange (CSE) except for those listed under the banks, finance, and insurance sectors over 163 months from September 2004 to March 2018. Nelson’s (1991) Exponential Generalized Autoregressive Conditional Heteroskedasticity (EGARCH) models are used to estimate the idiosyncratic volatility of individual stocks. The empirical findings of the study confirm that the five-factor asset pricing model of Fama and French (2015) is less successful and failed to explain the stock returns in the presence of unsystematic risk in the Sri Lankan context. This finding yields striking evidence of the success of the five-factor asset pricing model in the presence of idiosyncratic volatility while it casts doubts on the applicability of such factor models in estimating the cost of equity of firms in the real world. Although the impact of idiosyncratic volatility on stock returns is well-researched in the finance literature, there is little structured research on how idiosyncratic volatility affects the performance of asset pricing models in the Sri Lankan context. This study fills this gap by investigating the performance of the five factor asset pricing model of Fama and French (2015) using the firms listed on the CSE. The research findings should help academia develop more pronounced asset pricing models while tackling the idiosyncratic volatility of stocks.
Keywords: Asset pricing; EGARCH; Five-factor model; Idiosyncratic volatility; Sri Lanka